The Emesis Trial: Depressive Glioma Patients Are More Affected by Chemotherapy-Induced Nausea and Vomiting - Dufner, Vera; Kessler, Almuth Friederike; Just, Larissa; Hau, Peter; Bumes, Elisabeth; Pels, Hendrik Johannes; Grauer, Oliver Martin; Wiese, Bettina; Löhr, Mario; Jordan, Karin; Strik, Herwig (Frontiers in Neurology, 2022)
Purpose: Patients with malignant brain tumors face a limited life expectancy and at the same time, they suffer from afflicting symptoms and undesired effects of tumor treatment. Apart from bone marrow suppression, standard chemotherapy with temozolomide causes nausea, emesis and loss of appetite. In this pilot study, we investigated how chemotherapy-induced nausea and vomiting (CINV) affects the patients’ levels of depression and their quality of life. Methods: In this prospective observational multicentre study (n = 87), nausea, emesis and loss of appetite were evaluated with an expanded MASCC questionnaire, covering ten days during the first and the second cycle of chemotherapy. Quality of life was assessed with the EORTC QLQ-C30 and BN 20 questionnaire and levels of depression with the PHQ-9 inventory before and after the first and second cycle of chemotherapy. Results: CINV affected a minor part of patients. If present, it reached its maximum at day 3 and decreased to baseline level not before day 8. Levels of depression increased significantly after the first cycle of chemotherapy, but decreased during the further course of treatment. Patients with higher levels of depression were more severely affected by CINV and showed a lower quality of life through all time-points. Conclusion: We conclude that symptoms of depression should be perceived in advance and treated in order to avoid more severe side effects of tumor treatment. Additionally, in affected patients, delayed nausea was most prominent, pointing towards an activation of the NK1 receptor. We conclude that long acting antiemetics are necessary to treat temozolomide-induced nausea.